2005
DOI: 10.1287/trsc.1040.0090
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Analysis and Algorithms for a Demand-Driven Refleeting Model for Aircraft Assignment

Abstract: xzhu@vt.edu} T he current airline practice in conducting fleet assignments is to begin assigning aircraft capacity to scheduled flights well in advance of departures. However, the accuracy of the passenger demand forecast improves markedly over time, and revisions to the initial fleet assignment become naturally pertinent when the observed demand differs considerably from the assigned aircraft capacities. The demand-driven refleeting (DDR) approach proposed in this paper offers a dynamic reassignment of aircra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Prior to describing our model, we present the following notation that is based on a standard timespace network representation for all the fleet types (for example, see Berge and Hopperstad 1993, Hane et al 1995, Sherali et al 2005). …”
Section: Model Description and Notationmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to describing our model, we present the following notation that is based on a standard timespace network representation for all the fleet types (for example, see Berge and Hopperstad 1993, Hane et al 1995, Sherali et al 2005). …”
Section: Model Description and Notationmentioning
confidence: 99%
“…As fleet assignment decisions need to be made well in advance of departures for the purpose of scheduling crews (although demand is highly uncertain at this point), Sherali et al (2005) proposed a mixed-integer programming demand-driven refleeting model to be solved subsequently under more accurate demand forecasts while considering pathlevel or itinerary-level demands as in Barnhart et al (2002), where the reassignments of aircraft to flight legs are limited within the same family of aircraft so as to preserve serviceability by the same 501 crew. The advantage of this approach lies in the potential utilization of a more accurate and detailed demand forecast as departure times approach.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a simulation study performed by United Airlines, considering only simple "swappable round-trip loops, 3 " exhibited high benefits of such demand-driven swapping strategies (in the order of $35-45 million per year); results from several Continental Airlines studies, again considering such loop swaps, are similar [4]. Consequently, it is not surprising that several airlines are studying such approaches, including American Airlines, Continental Airlines, United Airlines (with whom we have collaborated in our research), Austrian Airlines, Finnair, Lufthansa Airlines, and KLM [e.g., [4,8,16,19], and the references therein]. At this late swapping phase, only "simple" swaps are viable, such as the loop swaps studied by United Airlines and Continental Airlines, for the following reasons: (1) These swaps will have a small and localized impact on the original fleet assignment, reducing problems with operations and maintenance.…”
Section: Introductionmentioning
confidence: 84%
“…Flight leg re-fleeting changes the fleet type assigned to a flight leg with higher than planned demand to a larger aircraft type, and the fleet type assigned to a flight leg with lower than planned demand to a smaller aircraft type while still maintaining aircraft flow balance. Representative literature describing flight leg re-fleeting can be found in [6], [7], and [8]. In flight leg re-timing, flight departure and arrival times of a flight leg are altered to create new connecting itineraries through the hub to serve markets with higher than expected demands.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on models and solution approaches for the dynamic re-fleeting problem, [8] proposes to study the interaction between an original schedule and subsequent dynamic re-fleeting decisions. To our knowledge, the results of this study have not been reported to date.…”
Section: Introductionmentioning
confidence: 99%